Immunometabolic and Vascular Health Responses among High Endurance Trained Subjects - Fonseca, Henrique A.R.; Bittencourt, Celia Regina; Monteiro, Andrea Moreira; Fonseca, Francisco Antonio; Sanches, Lívia Rentas; Ferreira, Carlos Eduardo dos Santos; Neto, Antonio Martins Figueiredo; Gidlund, Magnus; Izar, Maria Cristina (International Journal of Sports Medicine, 2023)
In this study, we aimed to examine the impact of high endurance training on vascular health parameters and immune-endocrine responses against modified low-density lipoprotein (LDL) particles. This observational, cross-sectional study included high endurance-trained and healthy non-trained subjects. Vascular ultrasound was used to assess vascular health parameters based on carotid intima-media thickness and endothelial function (flow-mediated dilation). Enzyme-linked immunosorbent assays were used to measure interleukin (IL)-8 and IL-10, autoantibody isotypes anti-oxidized LDL (oxLDL) and anti-apolipoprotein B (ApoB-D) peptide. Plasma levels of the corticosterone and 17 α-hydroxyprogesterone hormones were analyzed by mass spectrometry. This study enrolled 96 subjects, of whom 44 were high endurance trained and 52 were healthy non-trained individuals. Smaller carotid intima-media thickness values were observed in the high-endurance trained than in the healthy non-trained males, while no differences were observed between female groups. Flow-mediated dilation measurements did not differ by training or sex. The humoral immune responses to IgG anti-oxLDL and IgM anti-ApoB-D autoantibodies showed an isotype imbalance between the high-endurance trained and the non-trained groups. Immunoendocrine parameters showed inverse correlations between 17 α-hydroxyprogesterone concentrations and carotid intima-media thickness measurements. Direct correlations were found between IL-10 concentrations and flow-mediated dilation measurements. Chronic high-endurance exercise modulates immune-endocrine and vascular health parameters, in a sex-dependent manner.
Keywords: exercise; humoral immunity; oxidized LDL; atherosclerosis; endothelium